Factors That Influence Customer Loyalty Through Customer Satisfaction Mediation At Bank Syariah Indonesia (BSI) - Cahyaningrum, Ditasari; Hasan, Irmayanti (Jurnal Ecogen, 2024)
The focus of this research is centered on providing high-quality customer service and Customer Relationship Management to customers, as well as the satisfaction generated by this strategy. Primary data from this research was collected through the use of research tools in the form of questionnaires filled in by previously selected samples. The study's demographic comprises customers of Bank Syariah Indonesia (BSI) located in the city of Malang. In order to determine the sample size for this study, Malhotra's (2009) method was implemented due to the unpredictability of the population size. Consequently, 225 samples were acquired in order to conduct this research. Utilizing Structural Equation Modeling Partial Least Square (SEM-PLS), this study was investigated. The results of this research demonstrate that customer loyalty and satisfaction are significantly influenced by the quality of service provided. Additionally, service quality can impact customer loyalty via the intermediary mechanism of customer satisfaction. Customer relationship management does not have a substantial impact on customer satisfaction and loyalty. Customer satisfaction and customer relationship management are both ineffective mediators of consumer loyalty. Customer loyalty is substantially impacted by variables pertaining to customer satisfaction.